Pitfalls associated with lipophilic fluorophore staining of extracellular vesicles for uptake studies. Issue 1 (1st January 2019) - Simonsen, Jens B.
ABSTRACT: Post-staining of extracellular vesicles (EVs) with lipid-anchored fluorophores (LAFs) such as PKH67 is a widely used strategy for studying EVs but it is associated with several pitfalls. The pitfalls discussed in this commentary are related to LAF labelling of non-EV species due to (1) lipoprotein contamination in EV samples, (2) desorption of the LAF reporters from vesicles into proteins and lipoproteins in blood and serum, and (3) the capability of the amphiphilic LAF compounds to form EV-like particles. Awareness of these challenges and developing solutions to overcome these are important to ensure that we make relevant interpretations when using LAFs to track EVs.